Wibu dan #KaburAjaDulu: Kesadaran Politik dan Aspirasi Migrasi Ke Jepang Menurut Mahasiswa Sekolah Vokasi UGM - Mery Kharismawati; Wahyu Handayani Setyaningsih; Wury Dwiwardani; Aufa Maulidya Kayyisa; Mutiara Samudra (Vocational College of Diponegoro University, 2026)
This study examines how the consumption of Japanese popular culture shapes fandom practices, interpretations of social phenomena, and aspirations for global mobility among wibu. Using a qualitative approach supported by an exploratory survey, the study was conducted among students at the Vocational School of Gadjah Mada University. The results indicate that anime consumption and engagement in fandom practices contribute to the formation of a cultural habitus that holds symbolic affinity with Japan. This habitus is reflected not only in entertainment preferences but also in how respondents interpret the #KaburAjaDulu phenomenon, which is understood as an expression of anxiety and criticism toward social conditions. Additionally, respondents expressed aspirations to live, study, or work in Japan. Drawing on Appadurai’s concept of imagination, this study demonstrates that exposure to Japanese popular culture not only shapes patterns of cultural consumption but also influences how fans imagine future possibilities and global mobility. This study affirms that wibu cannot be understood solely as an escapist phenomenon but rather as a cultural practice involving identity formation, social interpretation, and future orientation.